Glucosylglycerate is an osmotic solute and an extracellular metabolite produced by Streptomyces caelestis - Pospísl, S; Halada, P; Petrícek, M; Sedmera, P (Folia microbiologica, 2007)
Streptomyces caelestis DSM 40084 produces two osmolytes, viz. 2-O-(alpha-D-glucopyranosyl)-zeta-glyceric acid (GG) and trehalose. Both compounds were isolated and identified by nuclear magnetic resonance spectroscopy and mass spectrometry. A very sensitive regulation of the cell osmolytes was demonstrated in exponentially growing cultures. The intracellular levels of GG and trehalose increased 2x in response to a step change of medium osmolarity caused by 0.3% NaCl. 1H NMR analysis of the cell extracts did not confirm the presence of additional osmolytes. GG is a S. caelestis metabolite commonly released from the cells; its concentration reached 3 g/L during the cultivation in a yeast extract--(NH4)2SO4-glycerol medium. This is the first report on the occurrence of the ionic osmolyte GG in the genus Streptomyces and on its free excretion to the medium.
Keywords: osmolární koncentrace; extracelulární prostor; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; kyseliny glycerové; disacharidy; Glyceric Acids; Streptomyces; osmóza; Extracellular Space; Osmolar Concentration; glykosylace; Trehalose; trehalosa; Glycosylation; vodní a elektrolytová rovnováha; Osmosis; kultivační média; Disaccharides; Water-Electrolyte Balance; Culture Media